2015
DOI: 10.1093/eurheartj/ehv007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of functional tissue factor by neutrophil extracellular traps in culprit artery of acute myocardial infarction

Abstract: Neutrophils are involved in the pathophysiology of infracted coronary arteries in STEMI via NET structures. Platelets, activated by thrombin, are required for NET formation, while the integrity of NET scaffold contributes to the functionality of NET-bound TF. The blockage of NET formation or local neutralization of NET-mediated TF signalling constitutes candidate therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
365
1
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 361 publications
(406 citation statements)
references
References 26 publications
17
365
1
23
Order By: Relevance
“…NET generation, preparation, and visualization by immunofluorescence confocal microscopy were performed as previously described (19). Samples were stained using anti-MPO MAb, anti-LL-37 MAb, or anti-NE polyclonal Ab.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NET generation, preparation, and visualization by immunofluorescence confocal microscopy were performed as previously described (19). Samples were stained using anti-MPO MAb, anti-LL-37 MAb, or anti-NE polyclonal Ab.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify NET release by ex vivo-or in vitro-stimulated PMNs, MPO-DNA complex was measured in NET structures isolated from 1.5 ϫ 10 6 PMNs as previously described (19) or in plasma from patients and control individuals. More specifically, capture antibody, 5 g/ml of anti-MPO MAb (Upstate, Millipore), was used to coat 96-well plates (dilution, 1:500 in 50 l) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…135 Recent evidence of a definitive role of NETs in venous and arterial thrombosis is now emerging. Circulating free DNA and NETs were detected in patients with primary antiphospholipid antibody syndrome, 149 within the clot of thrombosed stents, 150 and in thrombotic material isolated from coronary arteries during acute myocardial infarction, 151 the latter which were decorated with TF. Finally, at surgery or autopsy, NETs have been localized to human venous thrombi.…”
Section: Neutrophil Extracellular Trapsmentioning
confidence: 99%
“…NETs have been first described in 2004 as a new anti-microbial function of neutrophils [10] and consist of extracellular chromatin fibres decorated with various neutrophilderived granular, cytoplasmic and nuclear proteins. Since 2009, insightful studies demonstrated the involvement of this mechanism in the pathophysiology of various non-infectious disorders such as autoimmunity [11], autoinflammation [12], thrombosis [13,14] and cancer [15]. Kambas and colleagues provided the first evidence indicating a significant role for neutrophils in the pathophysiology of fibrosis [9].…”
Section: Introductionmentioning
confidence: 99%